LB0001 Intradiscal glucocorticoid injection for patients with chronic low back pain associated with active discopathy: a randomized trial. (15th June 2017) - Nguyen, C; Boutron, I; Baron, G; Sanchez, K; Palazzo, C; Benchimol, R; Paris, G; James-Belin, E; Lefèvre-Colau, M-M; Beaudreuil, J; Laredo, J-D; Béra-Louville, A; et al.
Abstract : Background: Active discopathy is associated with a specific phenotype of chronic low back pain (cLBP). Local inflammation has a role in active discopathy-associated symptoms (1). Objectives: To assess the efficacy of a single glucocorticoid intradiscal injection (GC IDI) in cLBP patients with active discopathy. Methods: We conducted a prospective, parallel-group, double-blind, randomized controlled study in 3 tertiary care centers in France. 135 cLBP patients with active discopathy on MRI were enrolled. They received a single GC IDI (25 mg prednisolone acetate) during discography (n=67) or discography alone (n=68). The primary outcome was the percentage of patients with LBP intensity in the previous 48 hr <40 on an 11-point numeric rating scale (NRS, 0 no pain - 100 maximal pain) at 1 month. The main secondary outcomes were LBP intensity and persisting active discopathy on MRI at 12 months post-intervention, and spine-specific limitations in activities, health-related quality of life, anxiety and depression, employment status and analgesics and non-steroidal anti-inflammatory drugs consumption at 1 and 12 months. Results: All randomized patients were included in the primary efficacy analysis. At 1 month, the percentage of responders (LBP intensity <40) was higher in the GC IDI than control group (36/65 [55.4%] vs 21/63 [33.3%]; absolute risk difference [95% confidence interval] 22.1 [5.5;38.7]); p=0.009. In the sensitivity analysis, mean reduction [95% CI] in LBP intensity from baseline to 1 month was greater in the GC IDI group compared to the control group (-32.5 [-38.2;-26.8] vs -17.5 [-23.3;-11.7], respectively; absolute difference [95% CI] -15.0 [-22.9;-7.1], p<0.001). At 1 month, the percentage of patients reporting an improvement in spine-specific limitations in activities was higher in the GC IDI than control group (55/65 [84.6%] vs 34/63 [54.0%]; absolute risk difference [95% CI] 30.5 [15.7; 45.2], p<0.001). The 2 groups did not differ in LBP intensity at 12 months and in most of the secondary outcomes at 1 and 12 months. 102/119 (85.7%) patients would agree to a second intervention. We found no cases of rapidly destructive disc disease or intervertebral disc calcifications. Conclusions: In active discopathy-associated cLBP, a single GC IDI reduces LBP at 1 month post-intervention but not at 12 months. Registration: ClinicalTrials.gov number NCT00804531 (First received: December 8, 2008. Last updated: June 23, 2016). References: Nguyen C, Poiraudeau S, Rannou F. From Modic 1 vertebral-endplate subchondral bone signal changes detected by MRI to the concept of 'active discopathy'. Ann Rheum Dis. 2015 Aug;74(8):1488–94. Acknowledgements: The study was funded by a research grant from the French Ministry of Health (Programme Hospitalier de Recherche Clinique, project no. P070157). The authors thank URC-CIC Paris Descartes Necker/Cochin (Christelle Auger and Nellie Moulopo) for implementation, monitoring and data management of the study. Disclosure of Interest: None declared